Risk assessment for Big Data in cloud computing: trust as an impact - Yusof Ali, Hazirah Bee; Abdullah, Lili Marziana; Kartiwi, Mira; Nordin, Azlin (2019)
Reduced IT cost, scalability, business continuity, collaboration efficiency and flexibility of work practice are some of the benefits that attract companies to move their business operation into the cloud. Cloud computing serves companies as IaaS, PaaS, and SaaS. Even though cloud has many benefits, it also has its own risks, the risk of being exposed unnecessarily as the cloud is owned and managed by a third party. Therefore, the risks need to be monitored and accessed by companies as they are the cloud customers who choose to use the cloud computing environment in handling their big data. Thus, the objective of this paper is to assess risk using trust measure as the impact.